Service Performance Measurement Using the Supply Chain Operation Reference Model in The Events and Travel Industry - Wurjaningrum, Febriana; Adienya, Gigih (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study aims to measure the performance of supply chain services using the Supply Chain Operation Reference (SCOR) Version 11.0 model in the events and travel industry. Design/Methods/Approach: The Supply Chain Operation Reference (SCOR) version 11.0 framework was employed to measure the performance of supply chain services. The performance indicators were assigned weights using the Analytical Hierarchy Process in Expert Choice Software. The performance achievements were marked using the traffic light system method, and an Action Plan was suggested for the company to improve its performance. Findings: The present study found 17 performance indicators consisting of 4 Plan performance attributes, 5 Source performance attributes, 3 Make performance attributes, 2 Deliver performance attributes, 2 Return performance attributes, and 1 Enable performance attribute. The weighting of each indicator resulted in the weight values for each activity from highest to lowest order, namely, Plan (0.317), Enable (0.297), Deliver (0.225), Source (0.95), Make (0.44), and Return (0.22). The performance measurement using a scoring system with the "larger is better" method and marking achievements through the traffic light system resulted in the company's aggregation value of 78%, indicating that the company still needs improvements in its supply chain service process even though the company's performance achievement is quite good. Originality: This research presents a new perspective on using SCOR-based performance measurement in service companies to become the basis for strategic decision-making and lead companies to achieve their competitive capabilities. Practical/Policy implication: The SCOR framework in every company business activity will provide a comprehensive view of the service supply chain as evaluation material for the company's service supply chain.